2022
DOI: 10.1021/acsaem.2c01749
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Interconnecting Layer for Monolithic Perovskite/Organic Tandem Solar Cells with Enhanced Outdoor Stability

Abstract: Photovoltaics with monolithically connected tandem architectures have the potential to achieve high efficiencies owing to enhanced spectral absorption and reduced thermal losses. To achieve this, photoactive layers with complementary absorption and interconnecting layers, which are robust, transparent, and energetically suitable, are essential. Here, we investigate a strategy to create an efficient, highly transparent, ohmic, and chemically robust interconnecting layer based on atomic layer-deposited tin oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Reproduced with permission. [ 77 ] Copyright 2022, American Chemical Society. (E) Schematic representation of the perovskite‐organic tandem device structure with ALD SnO x /Au functioning as recombination center.…”
Section: Interconnecting Layer In Perovskite‐organic Tscsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [ 77 ] Copyright 2022, American Chemical Society. (E) Schematic representation of the perovskite‐organic tandem device structure with ALD SnO x /Au functioning as recombination center.…”
Section: Interconnecting Layer In Perovskite‐organic Tscsmentioning
confidence: 99%
“…Reproduced with permission. [ 77 ] Copyright 2022, American Chemical Society. (G) Design of perovskite‐organic tandem cell structure with a highlight on a simplified ICL design and (H) J–V curves of the champion tandem device with different scan directions.…”
Section: Interconnecting Layer In Perovskite‐organic Tscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [ 69 ] Copyright 2022, American Chemical Society. d) Long‐term stability of POTSCs under the illumination of a 5 mW cm −2 365 nm UV light (N 2 glovebox).…”
Section: Device Stabilitymentioning
confidence: 99%
“…[77] As shown in Figure 10c, Xu et al found that, in the tandem configuration, WPSC is protected by the stack of ICL and the whole back cell from the diffusion of the top Ag electrode. [69] The interaction between the metal carrier recombination layer (Ag) and PEDOT:PSS is a major source of instability within tandem devices.…”
Section: Device Stabilitymentioning
confidence: 99%